PLANT RESIDUE BASED-COMPOSTS APPLIED IN COMBINATION WITH TRICHODERMA ASPERELLUMIMPROVE CACAO SEEDLING GROWTH IN SOIL DERIVED FROM NICKEL MINE AREA - A. Rosmana; R. Sakrabani; S. Sjam; N. Nasaruddin; A. Asman; B. Y. S. Pandin (Journal of Animal and Plant Sciences, 2019)
Cacao is widely grown in Sulawesi close to areas of nickel (Ni) mines indicating a possibility that the plant is affected by this heavy metal. By using soil collected from a Ni mining area, we evaluated three compositions of composted plant residues  consisting of firstly gliricidia, billy goat, and rice straw, secondly gliricidia,  stalk of palm oil fruit, and rice straw, and thirdly gliricidia, coconut husk, and rice straw, without and with addition of Trichoderma asperellum, in supporting growth of cacao seedling. Treatment with the respective compost types without any addition of T. asperellum caused an increase of seedling height by 18.9%, 28.5%, and 43.8%, stomata opening area by 17.2%, 4.3%, and 41.3%, stomata number by 13.4%, 22.7%, and 14.3%, and leaf Ni content by 3.8%, 12.8%, and 48.8% respectively. Following treatment with the three compost types included T. Asperellum, the increase of seedling height was 36.5%, 45.3%, and 54.7%, stomata opening area 15.9%, 21.3%, and 53.5%, stomata number 5.4%, 7.1%, and 0.0% and leaf Ni content 25.1%, 87.8%, and 161,4% respectively. Leaf analysis indicated that nitrogen content was increased when treated by the combination of composted plant residues and T. asperellum, potassium was increased in all treatments without T. asperellum, while phosphorus was decreased in all treated seedlings. These data suggest that one cause of cacao seedling growth improvement in soil containing Ni by composted plant residues and its combination with T. asperellum was the increase of Ni levels in leaves. Composts treatment could therefore potentially be used for cacao field application around Ni mining areas
Keywords: plant residues composition; plant height; stomata; nickel content; Trichoderma